Design of an electrochemical flow reactor prototype to the electro-oxidation of amoxicillin in aqueous media using modified electrodes with transition metal oxides. Issue 2 (April 2022) - Castro, J.A.; López-Maldonado, J.T.; Cárdenas, J.; Orozco, G.; Bustos, E.; Rivera, F.F.
Abstract: This research study integrated the development of modified large-size catalytic electrodes while employing painting and electrophoresis for Ti anodes and a proposed cylindrical reactor design using computational fluid dynamics (CFD) and experimental characterization tests. These development studies explored flow-by and parallel flow reactor configurations to remediate aqueous Amoxicillin (AMX). Simulation studies suggested that the velocity magnitude field and resident time distribution (RTD) curves were improved when the parallel flow configuration was employed. These findings followed based on the width and tail of the calculated RTD when both configurations were considered. The improved behaviors were associated with the avoiding of canalization or low-velocity stagnation zones in the reactor. Additionally, in the parallel flow configuration, the RTD curve maximum was reached near the dimensionless time, θ = 1, when general laminar flow rates (Re of 85 and 113) were used. Through both calculated potential and current distributions, in the parrel flow system, the potential field has a uniform distribution in the flow direction, with minimal edge formation. Since flow and electrical simulation suggested that the parallel flow configuration is better able to perform an electrochemical process, it was chosen and a processor was constructed. The constructed prototype achieved a maximum degradation efficiency of 92.3% (COD), and abatement of acute toxicity, in the reactor equipped with an electrophoretic modified anode, employing a current density of 7.5 A m −2 . Graphical Abstract: ga1 Highlights: IrO2 -Ta2 O5 |Ti (70:30) anode showed the highest electro-oxidation of amoxicillin in acid media. The electrophoretic technique to modify the anodes showed the highest mechanical stability than painting. Computational fluid dynamics studies were addressed to the electrochemical flow reactor design. The electrochemical flow parallel reactor showed the best diffusional control during the degradation of amoxicillin. The electrochemical flow parallel reactor achieves a removal efficiency of 92.3% using 7.5 A m -2 .